The management of thrombosis in pregnancy: Role of low-molecular-weight heparin - Kher, André; Bauersachs, Rupert; Nielsen, Jorn Dalsgaard (Thrombosis and Haemostasis, 2007)
Fatal pulmonary embolism remains the most common cause of mortality among pregnant women in many Western countries. The physiological changes of pregnancy produce a hypercoagulable state that increases the risk of venous thromboembolism (VTE).Women with inherited or acquired thrombophilias are at particularly high risk of VTE during pregnancy, and thromboprophylaxis may be advisable in some cases. Thrombophilia is also associated with complications of pregnancy, including fetal loss, pre-eclampsia, intra-uterine growth restriction, and placental abruption. The antithrombotic agents available for the prevention and treatment of VTE during pregnancy, and pregnancy complications, include unfractionated heparin (UFH), low-molecular-weight heparin (LMWH) and aspirin. Vitamin K antagonists are contra-indicated in pregnancy. Low-dose aspirin may have a role in the prevention of some pregnancy complications, although its safety in early and late pregnancy is uncertain. The efficacy and safety of LMWHs have been demonstrated for the prevention and treatment of VTE in pregnancy. These agents are increasingly being used in place of UFH, which is associated with a higher incidence of side effects compared with LMWH, in addition to the need for regular laboratory monitoring. Evidence is also emerging to support the use of LMWH in the prevention of recurrent fetal loss, although further trials are needed to explore the role of LMWHs in this indication and in the prevention of other complications of pregnacy.
Keywords: Pregnancy; low-molecular-weight heparin; thrombophilia; venous thrombosis